The effect of predict-observe-explain (POE) learning model using open-ended problem (OEP) towards students’ mathematical problem solving skill - I Made Aldy Setyadi; I Gusti Putu Sudiarta; Ni Made Sri Mertasari (Universitas Pendidikan Ganesha, 2019)
The research aims to determine disverification of the students’ mathematical problem solving skill differences with Predict-Observe-Explain (POE) learning model using open-ended problem (OEP), students who are using POE learning model and students who following conventional learning. This research is quasi-experiment with post-test only control group design. The population that is observed in this research is students of Senior High School number 5 Denpasar 2018/2019 school year in eleventh grade. Sample which has been picked is 3 classes using cluster random sampling thecnic. There are from 3 classess have been chosen 2 classes are being experimental classes and 1 class is a control class. Students’ mathematical probem solving skill measures using mathematic problem solving skill test. Data which is gained analyzed using one way ANAVA to find out first hypothesis and continued with scheffe test. Hypothesis test result showed that: firstly, there are differences of mathematical problem solving skills between students who used POE learning model using open-ended problem and students who followed conventional learning method (F_count=19,24 and F_table=3,08 ; F_count>F_table); secondly, students’ mathematical problem solving skill by the students who use POE learning model is better than students who following conventional learning (F_scheffe=10,43 and F'=6,16 ; F_scheffe>F'); third, students’ mathematic problem solving skill with POE learning model using open-ended problem is better than the students who followed conventional method konvensional (F_scheffe=9,09 and F'=6,16 ; F_scheffe>F'); fourth, students’ mathematic problem solving skill using POE learning model using open-ended problem is better than the students who only got conventional learning (F_scheffe=38,46 and F'=6,16 ; F_scheffe>F'). It can be concluded that POE learning model using open-ended problem give influence towards students’ mathematical problem solving skill.